ANALISA PELUANG DAN STRATEGI UKM dan UMKM DI ERA DIGITAL 4.0 BAGI MASYARAKAT SORKAM TENGAH - Nur Simamora, Fauziah; Ahmad Hutagalung, Jeniusman; Hutagalung, Heriyawan (COVIT (Community Service of Tambusai), 2023)
As UKM and UMKM, they must be worried about being displaced due to increasingly tight competition in business. can be seen from the fundamental challenges in the industrial world such as logistics costs, energy costs, and other things that affect production costs. But actually there is nothing that MSMEs or businesses with a larger scale need to fear. The existence of UMKM in rural areas also needs to be maintained, so that they can absorb productive age workforce. This can be done simultaneously with creating a transformation in marketing the form of business it has, especially UMKM. Sorkam is a sub-district in Central Tapanuli Regency, North Sumatra, Indonesia. The capital of this sub-district is in the Sorkam sub-district. The population of this sub-district in 2021 is 16,511 people, with a population density of 205 people/km². the people in Sorkam Tengah village have home-based businesses such as cassava chips, chips made from salted fish, and various types of Sorkam specialties. This is a local product that needs to be developed by utilizing the results of natural sources that support the regional economy. Keywords: UKM and UMKM, business opportunities, Revolution 4.0